The telomere effect : a revolutionary approach to living younger, healthier, longer - Blackburn, Elizabeth H. (Elizabeth Helen), 1948-; Epel, Elissa (Grand Central Publishing, 2017)
"Have you wondered why some 60-year olds look and feel like 40-year-olds and why some 40-year-olds look and feel like 60-year-olds? While many factors contribute to aging and illness, Nobel Prize-winning Doctor Elizabeth Blackburn discovered biological markers, called telomerase, the enzyme that replenishes telomeres, which protect our DNA Dr. Blackburn discovered that the length and health of one's telomeres provides a biological basis for the long hypothesized mind-body connection. But perhaps more importantly, along with leading health Psychologist, Dr. Elissa Epel, discovered that there are things we can do to improve and lengthen our telomeres to keep us vital and disease-free,"--NoveList.